A STUDY OF MIDDLE ADOLESCENCE IDENTITY OF SECONDARY SCHOOL STUDENTS - Boonchaiyuttasak, Jatuporn; Saleemad, Khanittha; Jamjuree, Danulada (Journal of Social Science and Cultural, 2024)
Middle adolescent identity of secondary school students is crucial for their growth into adults, as they will need to navigate life alongside diverse individuals in terms of gender, age, appearance, religion, and culture. This involves leading a life in society by demonstrating appropriate behaviors and reflecting the social development of adolescents. In enhancing the identity of students at the secondary school level, post-modern ideas are used that focus on learning to live together in society. Along with developing one's identity from criticizing what is happening in society, then revisiting, and changing one's identity through reflection from society. To lead to appropriate expression in society within the environment and context in which teenagers live. The research objectives are: 1) to study the middle adolescent identity of secondary school students, and 2) to examine behaviors indicative of the middle adolescent identity of secondary school students. In this used a qualitative research method, data were collected from documents, textbooks, academic journals, and relevant research, along with interviews with 16 students and their parents. The study finds that the middle adolescent identity of secondary school students refers to behavioral expressions resulting from their understanding of themselves in the societal context. It involves interpreting, assessing, and decision-making to create suitable options for expression in society, comprising three components: 1) Know your self, 2) Know your society and 3) Know your expression and Behaviors indicating The middle adolescent identity of secondary school students consist of ten behaviors indicating. The middle adolescent identity of secondary school students is significant for shaping their own identity through language and practices existing in society.